PFN2 and GAMT as common molecular determinants of axonal Charcot-Marie-Tooth disease. Issue 8 (15th February 2018) - Juneja, Manisha; Azmi, Abdelkrim; Baets, Jonathan; Roos, Andreas; Jennings, Matthew J; Saveri, Paola; Pisciotta, Chiara; Bernard-Marissal, Nathalie; Schneider, Bernard L; Verfaillie, Catherine; Chrast, Roman; Seeman, Pavel; et al.
Abstract : Background: Charcot-Marie-Tooth type 2 (CMT2) neuropathy is characterised by a vast clinical and genetic heterogeneity complicating its diagnosis and therapeutic intervention. Identification of molecular signatures that are common to multiple CMT2 subtypes can aid in developing therapeutic strategies and measuring disease outcomes. Methods: A proteomics-based approach was performed on lymphoblasts from CMT2 patients genetically diagnosed with different gene mutations to identify differentially regulated proteins. The candidate proteins were validated through real-time quantitative PCR and western blotting on lymphoblast samples of patients and controls, motor neurons differentiated from patient-derived induced pluripotent stem cells (iPSCs) and sciatic nerves of CMT2 mouse models. Results: Proteomic profiling of patient lymphoblasts resulted in the identification of profilin 2 (PFN2) and guanidinoacetate methyltransferase (GAMT) as commonly downregulated proteins in different genotypes compared with healthy controls. This decrease was also observed at the transcriptional level on screening 43 CMT2 patients and 22 controls, respectively. A progressive decrease in PFN2 expression with age was observed in patients, while in healthy controls its expression increased with age. Reduced PFN2 expression was also observed in motor neurons differentiated from CMT2 patient-derived iPSCs and sciatic nerves of CMT2 mice when compared with controls. However, no change in GAMT levels was observed in motor neurons and CMT2 mouse-derived sciatic nerves. Conclusions: We unveil PFN2 and GAMT as molecular determinants of CMT2 with possible indications of the role of PFN2 in the pathogenesis and disease progression. This is the first study describing biomarkers that can boost the development of therapeutic strategies targeting a wider spectrum of CMT2 patients.